2008
DOI: 10.1152/ajpheart.01115.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ω-hydroxylase product on distal human pulmonary arteries

Abstract: Morin C, Guibert C, Sirois M, Echave V, Gomes MM, Rousseau E. Effects of -hydroxylase product on distal human pulmonary arteries. Am J Physiol Heart Circ Physiol 294: H1435-H1443, 2008. First published January 18, 2008 doi:10.1152/ajpheart.01115.2007The aim of the present study was to provide a mechanistic insight into how 20-hydroxyeicosatetraenoic acid (20-HETE) relaxes distal human pulmonary arteries (HPAs). This compound is produced by -hydroxylase from free arachidonic acid. Tension measurements, perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…To perform these experiments, human lung tissues from patients undergoing surgery for lung carcinoma and distant from the malignant lesion were obtained. Pulmonary arteries of similar weight and length (inner diameter of 0.5 -0.8 mm) were micro-dissected and placed in culture for 24 hours in a humidified incubator at 37C under 5% CO 2 as previously reported (Guibert et al, 2005, Morin et al, 2008. Resulting data demonstrated that 20-HETE acts as a potent vasodilator on HPA pre-contracted with 5-HT and phenylephrine (PE) (Figure 2A, Morin C et al, 2008).…”
Section: Role Of Cyp450-dependent Arachidonic Acid Metabolites In Pulmentioning
confidence: 58%
See 4 more Smart Citations
“…To perform these experiments, human lung tissues from patients undergoing surgery for lung carcinoma and distant from the malignant lesion were obtained. Pulmonary arteries of similar weight and length (inner diameter of 0.5 -0.8 mm) were micro-dissected and placed in culture for 24 hours in a humidified incubator at 37C under 5% CO 2 as previously reported (Guibert et al, 2005, Morin et al, 2008. Resulting data demonstrated that 20-HETE acts as a potent vasodilator on HPA pre-contracted with 5-HT and phenylephrine (PE) (Figure 2A, Morin C et al, 2008).…”
Section: Role Of Cyp450-dependent Arachidonic Acid Metabolites In Pulmentioning
confidence: 58%
“…However, 20-HETE has been shown to be an eicosanoid product of human lung tissue that acts as a potent vasodilator of isolated pressurized pulmonary arteries (Birks et al, 1997, Morin et al, 2008. Furthermore, cytochrome P-450 4A (CYP4A) protein is expressed in the pulmonary vasculature, a finding based on Western blots of PA microsomes (Zhu et al, 1998), the conversion of arachidonic acid into 20-HETE by dispersed vascular smooth muscle cells (Zhu et al, 1998), and immunohistochemistry localizing CYP4A to rabbit pulmonary capillary endothelium (Roman et al, 1993).…”
Section: Role Of Cyp450-dependent Arachidonic Acid Metabolites In Pulmentioning
confidence: 99%
See 3 more Smart Citations